Pemanfaatan Media Pembelajaran IPA terhadap Hasil Belajar Siswa Kelas V di SD Negeri 091 Palembang - Samian Hakim; Lukman Hakim; Treny Hera (Departement of Mathematics Education, 2023)
This study aims to determine the influence of the use of science learning media on the learning outcomes of grade V students at SD Negeri 091 Palembang. In this study, it uses the experimental research method